Religiosity, Spirituality, and HIV Risk Behaviors among African American Women from Four Rural Counties in the Southeastern U.S - Ludema, Christina (J Health Care Poor Underserved, 2015)
In a cross- sectional survey of 1,013 African American women from rural Alabama and North Carolina, we examined the relationship of (1) organizational religiosity (i.e., religious service attendance), (2) non- organizational religiosity (e.g., reading religious materials), and (3) spirituality with these outcomes: women’s reports of their sexual behaviors and perceptions of their partners’ risk characteristics. Women with high non-organizational religiosity, compared with low, had fewer sex partners in the past 12 months (adjusted prevalence ratio (aPR): 0.58, 95% confidence interval (CI): 0.42, 0.80) and were less likely to have concurrent partnerships (aPR: 0.47, 95% CI: 0.30, 0.73). Similar results were observed for spirituality, and protective but weaker associations were observed for organizational religiosity. Weak associations were observed between organizational religiosity, non- organizational religiosity, and spirituality with partners’ risk characteristics. Further exploration of how religiosity and spirituality are associated with protective sexual behaviors is needed to promote safe sex for African American women.